2012
DOI: 10.1016/j.jml.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval failure contributes to gist-based false recognition

Abstract: People often falsely recognize items that are similar to previously encountered items. This robust memory error is referred to as gist-based false recognition. A widely held view is that this error occurs because the details fade rapidly from our memory. Contrary to this view, an initial experiment revealed that, following the same encoding conditions that produce high rates of gist-based false recognition, participants overwhelmingly chose the correct target rather than its related foil when given the option … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 47 publications
6
43
1
Order By: Relevance
“…The primary factor determining whether critical diagnostic perceptual details can be retrieved from memory and gist-based false recognition can be suppressed is whether the target item is made available as a cue on the recognition test. Attention to the perceptual details that are relevant to the discrimination, which does not result in retrieval of the target item, is not sufficient (see Guerin et al, 2012, for further discussion). These findings also complement Tulving’s observations of the effects of similarity in forced-choice recognition: in general, the similarity among test items on a recognition test is a less important determinant of performance than the similarity of the test items to information that is stored in memory (Tulving, 1981; see also Busey et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary factor determining whether critical diagnostic perceptual details can be retrieved from memory and gist-based false recognition can be suppressed is whether the target item is made available as a cue on the recognition test. Attention to the perceptual details that are relevant to the discrimination, which does not result in retrieval of the target item, is not sufficient (see Guerin et al, 2012, for further discussion). These findings also complement Tulving’s observations of the effects of similarity in forced-choice recognition: in general, the similarity among test items on a recognition test is a less important determinant of performance than the similarity of the test items to information that is stored in memory (Tulving, 1981; see also Busey et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we dissociated attention to specific perceptual detail and successful retrieval of specific perceptual detail. We accomplished this goal using a paradigm we recently developed that shows that gist-based false recognition, which occurs when one mistakenly recognizes an item that is similar to an item that was previously encountered (Reyna and Brainerd, 1995; Koutstaal and Schacter, 1997), occurs primarily because of a failure to retrieve detailed information that is still stored in memory (Guerin et al, 2012). Critically, our data established that attention to the specific perceptual details relevant to the task is not sufficient to overcome this failure.…”
Section: Introductionmentioning
confidence: 99%
“…Across all three experiments, we found that the memory impairment only affected representations of items the participant had previously viewed. This restrained, object-specific memory impairment in long-term memory suggests that recognizing visual information from long-term memory is tightly focused and that any costs or benefits of recognizing information do not spread to other visual representations in a category (see Guerin et al, 2012 for evidence of a similar object-specific memory).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studying a dozen pictures of cats leads one to remember quite well that cats were studied, but can hinder one’s ability to recall perceptual details of particular cats and thus to discriminate novel pictures of cats from studied pictures of cats. Stimulus characteristics, instructions, and test conditions all can influence reliance on gist-based responding (Guerin, Robbins, Gilmore, & Schacter, in press; Koutstaal & Cavendish, 2006; Koutstaal et al, 2003; Koutstaal, Schacter, Galluccio, & Stofer, 1999; Tun, Wingfield, Rosen, & Blanchard, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…The semantic categorization account maintains that pre-existing semantic associations can overshadow the use of item-specific features, and is predicated on the finding that studying sets of concrete, but not abstract, pictures increases levels of false recognition (Koutstaal, et al, 2003). Retrieval processes contribute substantially to gist-based errors (Guerin et al, in press), as disambiguating perceptual information is adequately encoded to at least some extent (Koutstaal, 2003), and can be made accessible under appropriate retrieval conditions (Guerin et al, in press). In addition, encountering many overlapping perceptual features can reinforce the representation of prototypical features (e.g., the shape features that are generally shared across exemplars from the category “chair”) which then, as a result of flexible recombination or binding of features by a constructive memory system, could seem familiar in a novel exemplar that shares those same prototypical features.…”
Section: Introductionmentioning
confidence: 99%